2006
DOI: 10.1021/je060380p
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Anthracene in Binary Diisopropyl Ether + Alkane Solvent Mixtures at 298.15 K

Abstract: Experimental solubilities are reported for anthracene in six binary diisopropyl ether + alkane solvent mixtures at 298.15 K. The alkane solvents studied were hexane, heptane, octane, cyclohexane, methylcyclohexane, and 2,2,4-trimethylpentane. Results of these measurements were used to test a mathematical representation based on the combined nearly ideal binary solvent (NIBS)/Redlich-Kister equation. For the six systems studied, the combined NIBS/Redlich-Kister equation was found to accurately describe the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…From the standpoint of a polarizable continuum model, all four organic solvents should solvate a given solute equally well. In reality, however, numerous studies of solute solubility and partitioning have shown that the identity of the alkane solvent can affect the solvent’s ability to solvate a solute. ,,, Results reported in Table are consistent with previous reports noting that partitioning coefficients of substituted phenols are significantly larger for cyclohexane/aqueous systems compared to linear alkane/aqueous systems, although the origins of these results have not been correlated with explicit solvent structure. , An analysis of the contribution made to Δ(Δ G solv ) by a Flory−Huggins volume dependence on solvation predicts that the largest organic solvent should favor larger (alkane/aqueous) partitioning coefficients through the following expression: Δ false( Δ G false) FH = R T ln false[ x false] alk false[ x false] aq R T true( V x V aq V x V alk true) where Δ(Δ G ) FH is a Flory−Huggins-based description of the change in solvation energy when a solute migrates from one phase to another, [ x ] i is the concentration of the solute in the alkane and aqueous phases, and V i are the molar volumes of the solute, water, and organic species. Given that V aq and V x are constant for a given solute (and greater than unity), and given that V aq will be much smaller than V alk , the largest alkane solvents will make the smallest (positive) contribution to Δ(Δ G ) FH .…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…From the standpoint of a polarizable continuum model, all four organic solvents should solvate a given solute equally well. In reality, however, numerous studies of solute solubility and partitioning have shown that the identity of the alkane solvent can affect the solvent’s ability to solvate a solute. ,,, Results reported in Table are consistent with previous reports noting that partitioning coefficients of substituted phenols are significantly larger for cyclohexane/aqueous systems compared to linear alkane/aqueous systems, although the origins of these results have not been correlated with explicit solvent structure. , An analysis of the contribution made to Δ(Δ G solv ) by a Flory−Huggins volume dependence on solvation predicts that the largest organic solvent should favor larger (alkane/aqueous) partitioning coefficients through the following expression: Δ false( Δ G false) FH = R T ln false[ x false] alk false[ x false] aq R T true( V x V aq V x V alk true) where Δ(Δ G ) FH is a Flory−Huggins-based description of the change in solvation energy when a solute migrates from one phase to another, [ x ] i is the concentration of the solute in the alkane and aqueous phases, and V i are the molar volumes of the solute, water, and organic species. Given that V aq and V x are constant for a given solute (and greater than unity), and given that V aq will be much smaller than V alk , the largest alkane solvents will make the smallest (positive) contribution to Δ(Δ G ) FH .…”
Section: Resultssupporting
confidence: 79%
“…One goal of these studies is to identify how different solute−solvent interactions correlate with observed partitioning behavior in alkane/aqueous systems. A property that provides insight into solute/solvent interactions is a solute’s solvatochromic response in different solvents. Solvatochromism refers to a solute’s solvent-dependent absorbance and/or emission spectra, and this property can be exploited to quantify local polarity around the solute ,,, or to calculate differences in permanent dipoles between a solute’s ground and excited electronic states. , Figure shows bulk solution absorbance maxima in a variety of solvents as a function of each solvent’s Onsager polarity function, f (ϵ), where f (ϵ) is related to a solvent’s static dielectric constant, ϵ, f ( ϵ ) = 2 ( ϵ 1 ) 2 ϵ + 1 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…58 appeared in print, there have been several experimental solubility studies involving anthracene dissolved in organic solvents. Acree and co-workers [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] have measured the solubility of anthracene in four linear alkanes (nonane through dodecane), in two dialkylbenzenes (1,2-dimethylbenzene and 1,3-dimethylbenzene), in several primary (methanol, ethanol, 1-pentanol, 2-methyl-1-butanol, 1-hexanol, 2-methyl-1-pentanol, 1-heptanol, 2-ethyl-1-hexanol, 1-decanol, 3,7-dimethyl-1-octanol, 1,2-ethanediol, and 2,2,2-trifluoroethanol), three secondary (2-pentanol, 4-methyl-2-pentanol, and cyclopentanol) and one tertiary (2-methyl-2-propanol) alcohol(s), in four alkyl alkanoates (methyl ethanoate, propyl ethanoate, pentyl ethanoate, and methyl butanoate), in three ethers (2,2′-oxybispropane, 2-methoxy-2-methylpropane, and 1,1′-oxybis[2-methoxyethane]), in three chlorinated alkanes (dichloromethane, trichloromethane, and 1-chlorohexane) and three halogenated benzenes (chlorobenzene, fluorobenzene, and (trifluoromethyl)benzene), in five alkoxyalcohols (2-ethoxyethanol, 2-propoxyethanol, 2-isopropoxyethanol, 2-butoxyethanol, and 3-methoxy-1-butanol) and in several miscellaneous organic solvents (methyl acetoacetate, ethyl acetoacetate, ethanenitrile, propanenitrile, butanenitrile, benzonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, morpholine, ethanolamine, propylene carbonate, hexanedintitrile (also called adiponitrile) and tributyl phosphate). The authors measured the solubility at only 298.15 K, and for most of the solvents there are no independent experimental measurements to compare the numerical values against.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%